(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
This paper examines the possibility o f using pattern recognition method, which is based on compositions of fuzzy relations, to work with multiple feature selections such as where the number o f features is greater than 3. Investigation o f problems, which are connected to multidimensional pattern recognition, is also applied. Some practical part concerning proposals on experiments is provided.